Kajian Agroekosistem Berkelanjutan Di Kawasan Hutan Kemasyarakatan (HKm) Kabupaten Lombok Tengah: Study of Sustainable Agroecosystems in Community Forest Areas (HKm) in Central Lombok Regency - Wulandari, Febriana; Shabrina, Hassyati (HUTAN TROPIKA, 2025)
Sustainable agroecosystem patterns in the Community Forest (HKm) area of Central Lombok Regency play an important role in maintaining ecosystem balance while improving the welfare of communities living around the forest. This study aims to analyze the agroecosystem patterns applied in the Aik Bual HKm and evaluate their effectiveness in supporting environmental and economic sustainability. The method used is a descriptive approach with secondary data analysis from various related studies. The results indicate that the agroecosystem in the HKm Aik Bual area adopts agroforestry, silvopasture, and ecosystem-based management systems, enabling improved soil fertility, reduced erosion, and diversified community income. The diversity of plant species and vegetation strata indicates positive indicators for ecosystem stability. Land management patterns using the agrosilvopasture system and random mixture cropping patterns provide significant ecological and economic benefits, despite challenges in resource management and agricultural mechanization. In conclusion, the agroecosystem patterns applied in the Aik Bual Community Forest contribute to increasing land productivity and community food and economic security, while maintaining environmental sustainability. Optimizing management and improving access to technology and information are essential to ensure the sustainability of this system